Asymmetric Responses of Wages on Unemployment Rate Changes - Klonowska-Matynia, Maria; Przekota, Grzegorz (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The essential scientific aim of this article will be estimate the strength and direction of reaction changes in nominal and real wages in Poland to changes in the unemployment rate. The research will aim at answering the following detailed questions: Is there a reaction in nominal and real wages changing on unemployment rate in Poland? How strong is the reaction and what kind of direction is this? Detailed analyses will be carried out with the following groups' data support: unemployment and rate, real and nominal wages in consecutive months of 2000 and 2011. Basis method used in article ECM Model with and without asymmetry.